Investigation on the effect of diethyl ether with hydrogen-enriched cashew nut shell (CNS) biodiesel in direct injection (DI) diesel engine. (1st October 2020) - Loganathan, M.; Madhavan, V.M.; Arun Balasubramanian, K.; Thanigaivelan, V.; Vikneswaran, M.; Anbarasu, A.
Abstract: The current research paper deals with the experimentation on direct injection diesel engine characteristics for different proportions of diethyl ether in diesel-hydrogen-cashew nut shell liquid blends. Initially, the optimized B20 (20% CNSL and 80% diesel) blend was tested with different proportions of hydrogen such as 4, 6 and 8 L per minute which were optimized at 6 lpm H2 flow rate. The diethyl ether, of 2%, 4%, and 6% proportions, is blended with B20 in which the 6 lpm H2 flow rate was maintained as constant. The experiments were conducted in a single-cylinder diesel engine with a constant speed of 1500 rpm. From the experimentation, it was revealed that the brake thermal efficiency got increased whereas the exhaust emission of both Carbon monoxide and hydrocarbon got decreased when H2 is added with CNSLB20. But the NOx emission got increased with H2 addition. Further, the 6 lpm H2 -CNSLB20 and diethyl ether with 6% blends exhibited 43% and 50% decrease respectively in hydrocarbon and CO emissions, when compared to CNSLB20. The brake specific fuel consumption got reduced up to 45% in the fuel combination mentioned above. Meanwhile, when DEE was added with 6 lpm H2 -CNSLB20 fuel combinations, the NOx emission, in-cylinder pressure, and heat release rate were increased.